2014
DOI: 10.1093/gji/ggu244
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic seismic anisotropy models within a slab impinging on the core–mantle boundary

Abstract: S U M M A R YThe lowermost few hundreds of kilometres of the Earth's mantle are elastically anisotropic; seismic velocities vary with direction of propagation and polarization. Observations of strong seismic anisotropy correlate with regions where subducted slab material is expected. In this study, we evaluate the hypothesis that crystal preferred orientation (CPO) in a slab, as it impinges on the core-mantle boundary, is the cause of the observed anisotropy. Next, we determine if fast polarization directions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 103 publications
(139 reference statements)
3
25
0
Order By: Relevance
“…Previous investigations of the source of anisotropy in the D″ have shown that the expected texture of bmg in D″ layer does not produce a seismic signature consistent with seismic observations and thus is not expected to contribute significantly to the observed seismic anisotropy in the region27. (Mg,Fe)O fp with high V s anisotropy of ∼40% and abundance of ∼25% volume in the D″ layer, has been suggested as a source for the observed anisotropy in D″ (ref.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous investigations of the source of anisotropy in the D″ have shown that the expected texture of bmg in D″ layer does not produce a seismic signature consistent with seismic observations and thus is not expected to contribute significantly to the observed seismic anisotropy in the region27. (Mg,Fe)O fp with high V s anisotropy of ∼40% and abundance of ∼25% volume in the D″ layer, has been suggested as a source for the observed anisotropy in D″ (ref.…”
Section: Discussionmentioning
confidence: 80%
“…Seismic velocities resulting from slip on (001)[100] and (001)[010] or on (001)<110> alone in a slab descending to the bottom of the mantle were predicted with a three-dimensional geophysical model27, which assumes deformation is accommodated by dislocation slip. Tracers in the model record temperature and strain history as the slab descends.…”
Section: Discussionmentioning
confidence: 99%
“…Ferropericlase may not only influence the development of crystallographic preferred orientation and seismic anisotropy more than previously thought (e.g. Cottaar et al, 2014), but mantle mixing (Girard et al, 2016), viscosity (Yamazaki and Karato, 2001) and slab stagnation (Marquardt and Miyagi, 2015) as well.…”
Section: Introductionmentioning
confidence: 90%
“…However, in general φ ′ is not the same for the two methods, and δt is smaller for the finite-frequency methodthough this δt relationship is not universally true, notably for the S2 path. This immediately implies that previous interpretations of flow direction or likely mechanisms for anisotropy in D ′′ using ray methods (e.g., Wookey et al 2005;Wookey & Kendall 2008;Long 2009;Nowacki et al 2010;He & Long 2011;Nowacki et al 2013;Cottaar et al 2014;) may need to be revisited, even in areas of apparently 'weak' and simple anisotropy.…”
Section: Isotropymentioning
confidence: 99%